Comercio ilegal de los recursos forestales maderables en la región Loreto, 2021 - Del Aguila Panduro, Iris Vanessa (2023)
This study was carried out in Loreto region, with the purpose of knowing the current state of the illegal trade of timber forest resources in Loreto region. Loreto is the largest producer of logs and has the highest rate of illegal extraction, reaching 70.88%, followed by Ucayali with 11.44% and Madre de Dios in third place with 11.33% (Pro etica, 2020). DS 013-2021-MIDAGRI (2021), indicates that the Local Forests modality is the one that mobilized the largest volume of illegal wood (unauthorized volume) with 661,825,179 m³ between the years 2015 and 2020, in second place, the contracts in CCNN and CCCC with 579,029.239 m³. The largest volume of illegal timber mobilized was in 2015 with 561,079.035 m³ and dropped considerably in 2019 to 75,954.50 m³. Peru has lost a total of 2,563,714 ha of forest and Loreto 288,250 ha of forest between 2001 and 2020. In 2020, Peru lost 203,272 ha of forest and Loreto 27, 850 ha (Geobosques, 2020). There is a relationship in the primary information obtained for the present investigation and the surveys and the interviews carried out, which on the vigesimal scale is approving, however there is a certain percentage of people (extractors and entrepreneurs) on which with training, visits to the forest and environmental education in general.